PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PESERTA DIDIK KELAS IV SD NEGERI 011 UJUNG BATU Rama Yana1, Elvina2 - Rama Yana; Elvina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to improve the learning outcomes of grade IV students of SD Negeri 011 Ujung Batu in Indonesian subjects by using a problem-based learning model. Some of the obstacles faced include (1) low learning achievement in Indonesian subjects and (2) the need for changes and improvements in learning through more effective methods. The method applied in this study is class action research (PTK). This study involved 22 grade IV students, consisting of 13 male students and 9 female students. This research was carried out in stages, starting from cycle I and continuing until the last cycle. with four components, namely planning, implementation, observation and reflection. The data collection instruments used were observation sheets, and learning outcome tests. The results of the research in the first cycle were only 65.83% of student activity and 75.95% of teacher activity. In cycle II, the average student activity was 84.16% and teacher activity was 86.53%. The results of the abilities obtained by students increased from an average of 63.63% in Cycle I to 86.35% in Cycle II. This indicates that the application of the problem-based learning (PBL) learning model can increase activities and achievements in Indonesian lessons at SDN 011 Ujung Batu.